Pola Kajian Hari Kiamat: Sorotan 30 Tahun Literatur Secara Sistematik (1988-2018) - Khairul Asyraf Mohd Nathir; Mohd Sukki Othman; Nik Farhan Mustapha; Wan Muhammad Wan Sulong (Universiti Teknologi Malaysia (UTM), 2024)
Indexed by MyCite